Careful Co-presence: The Transnational Mediation of Emotional Intimacy - Donya Alinejad (Social Media + Society, 2019)
This article investigates how migrants experience “co-presence” with their loved ones through social media. On the basis of empirical investigation, the article engages with current debates about how social media shape emotional experiences. It draws on short-term ethnographic research of everyday social media practices among second-generation Turkish-Dutch migrants who grew up in the Netherlands and migrated to Istanbul in adulthood. The article focuses on transnational family intimacy within this migration phenomenon as an in-depth case study for understanding the role of social media platforms and mobile devices in producing emotional experiences of togetherness under conditions of long-distance, long-term separation. The author shows how social media platforms afford not only ambient, fast-paced, background communications—which have been emphasized in the literature, thus far—but also more direct, immersive, conversational modes of communication. The article argues that people’s practices of carefully shifting between these modes of social media communication produce their experiences of transnational emotional intimacy. The author develops the notion of careful co-presence through a discussion of how social media practices that produce intimacy reflect both discerning selectivity and emotional care. This argument builds on scholarship that has advanced practice-based approaches to understanding how emotion is mediated through digital media.